A comparative study on the performances of the Boost PFC circuit - Sahid, Mohd. Rodhi; Azli, Naziha Ahmad; Muhammad, N. D. (IEEE, 2004)

(untitled)
Power Factor Correction (PFC) circuit using Boost converter for low power applications are developed and analyzed in this work. Average current mode control is utilized in this work to control the circuit in the closed loop system. Simulation is done for the Boost PFC circuit to validate the designed parameters. Furthermore, an experimental circuit is developed to verify and compare the results with the simulation. The frequency spectrum of the input current is then compared with the EN/IEC61000-2-3 Standard on Harmonic Distortion. The dynamic response of the Input current and output voltage are discusses as well. A 500W output load is first chosen to illustrate the performances of the circuit. Several values of output load and input voltage would conclude the overall performance of the circuit.